30 years of trade policy: Evidence from 5.7 billion tariffs - Feodora A. Teti (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper presents a new global tariff database covering tariffs at the six-digit product level for 197 importing countries and their trading partners for 30 years, namely 1988 to 2017. I deal simultaneously with the two major issues, missing data and misreporting, almost doubling the number of available tariffs from 2.9 to 5.7 billion. The improvement in the data is particularly relevant for developing countries. With this new dataset at hand I document numerous new facts about tariffs around the world improving our understanding of how countries set tariffs substantially.
Keywords: F13; F14; 330; tariffs; MFN; preferences